Rasionalitas Pemilih Prabowo–Gibran Dalam Pilpres 2024: Kajian Perspektif Elit Partai Politik Di Provinsi Lampung - Alamsyah, Anam; Zaimasuri, Zaimasuri (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2025)
This study aims to analyze the behavior of voters for the Prabowo-Gibran pair in the 2024 Presidential Election using rational choice theory as the main analytical framework. This pair's victory is interesting to study because it occurred amidst various negative issues such as legal controversies, accusations of nepotism, and political ethics, yet it actually gained significant electoral support. This study uses a qualitative approach with an in-depth interview method with ten informants consisting of elite political parties supporting and non-supporting, academics, and representative voters. Data analysis was conducted using thematic analysis techniques to find patterns of meaning from elite narratives. The results show that Prabowo-Gibran voter behavior is rational-pragmatic. Voters tend to assess the direct benefits offered by this pair, such as the continuity of development programs and political stability, rather than considering moral or ethical issues. In the context of rational choice, support for Prabowo-Gibran shows a realistic calculation of costs and benefits at the community level. This study concludes that voter rationality in Lampung is oriented towards practical benefits and the candidate's chances of victory.